Not Just a Laughing Matter Interdisciplinary Approaches to Political Humor in China (The Humanities in Asia,, 2018)
This book offers the first comprehensive and in-depth exploration of the way Chinese humor fits into broader discourses on Chinese identity and modernity in an increasingly globalized world throughout the period of modern China. It brings together the expertise of scholars from a variety of disciplines - history, literature, linguistics, anthropology, sociology and the study of popular culture - to examine the many forms and modes in which political humor is expressed in modern China: films, cartoons, the visual arts, oral performances and online satire.